2007
DOI: 10.1111/j.1464-410x.2007.07280.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute pyelonephritis: comparison of diagnosis with computed tomography and contrast‐enhanced ultrasonography

Abstract: OBJECTIVE To assess the value of contrast‐enhanced ultrasonography (US) with the contrast pulse‐sequence (CPS) technique for detecting renal parenchymal changes in acute pyelonephritis (APN), compared with contrast‐enhanced computed tomography (CT) as the reference standard. PATIENTS AND METHODS We examined 100 patients (82 women, 18 men; mean age 30.2 years, range 18–67); children (those aged <18 years) were excluded from the study. All patients had clinical symptoms suggestive of APN. For the US a Sequoia 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 17 publications
0
29
0
9
Order By: Relevance
“…Mitterberger et al concluded that CEUS allows small renal parenchymal changes in APN to be detected with high specificity (98%), sensitivity (100%) and moreover, without radiation exposure [10]. In several cases (diabetic or immunosuppressed patients) pyelonephritis can be complicated with parenchymal abscess formation.…”
Section: Renal Infections (Pyelonephritis or Renal Abscess)mentioning
confidence: 99%
“…Mitterberger et al concluded that CEUS allows small renal parenchymal changes in APN to be detected with high specificity (98%), sensitivity (100%) and moreover, without radiation exposure [10]. In several cases (diabetic or immunosuppressed patients) pyelonephritis can be complicated with parenchymal abscess formation.…”
Section: Renal Infections (Pyelonephritis or Renal Abscess)mentioning
confidence: 99%
“…Recently, it has been reported that computed tomography may be more useful than ultrasonography. Especially, the classification according to the degree of parenchymal invasion of the contrast enhancement computed tomography image is associated with the severity and prognosis of pyelonephritis [30][31][32][33].…”
Section: ) Laboratory Diagnosis: a Urinalysis (Dipstick Method) Is Rmentioning
confidence: 99%
“…[1,2,3] Kako zbog svoje široke dostupnosti, tako i zbog neškodljivosti i lake izvodljivosti, ultrasonografsko ispitivanje predstavlja prvi korak u dijagnostikovanju akutnog pijelonefritisa. [4,5] Medjutim, u studiji Craig WD i autora [6], ukazano je da upotreba CT-a, sa većom sigurnošću dokazuje akutni pijelonefritis, što smo mi i uzimali kao referentni zlatni standard zajedno sa aspiracioniom biopsijom tankom iglom. [7] Postoje mnogobrojni ehotomografski parametri koji ukazuju na akutni pijelonefritis.…”
Section: Diskusijaunclassified